2021
DOI: 10.3390/cancers13020191
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cyclic Pentadepsipeptide, N-Methylsansalvamide, Suppresses Angiogenic Responses and Exhibits Antitumor Efficacy against Bladder Cancer

Abstract: Here, we explored the anti-tumor efficacy of a cyclic pentadepsipeptide, N-methylsansalvamide (MSSV), in bladder cancer. MSSV inhibited the proliferation of both bladder cancer 5637 and T24 cells, which was attributed to the G1-phase cell cycle arrest, apoptosis induction, and alteration of mitogen-activated protein kinases (MAPKs) and protein kinase b (AKT) signaling pathways. Additionally, the treatment of bladder cancer cells with MSSV suppressed migratory and invasive potential via the transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Tumor angiogenesis can promote tumor cells to invade the blood system, thereby triggering tumor metastasis, which is one of the main obstacles to NSCLC treatment ( 34 ). Our results showed that 6h could suppress the production of MMPs (MMP-2 and MMP-9), thereby inhibiting the migration and invasion of NSCLC cells ( 35 ). Furthermore, the in vivo experiments proved that the tumor growth of nude mice was effectively inhibited after 6h treatment, and 6h did not cause detectable pathological abnormality of main organs.…”
Section: Discussionmentioning
confidence: 70%
“…Tumor angiogenesis can promote tumor cells to invade the blood system, thereby triggering tumor metastasis, which is one of the main obstacles to NSCLC treatment ( 34 ). Our results showed that 6h could suppress the production of MMPs (MMP-2 and MMP-9), thereby inhibiting the migration and invasion of NSCLC cells ( 35 ). Furthermore, the in vivo experiments proved that the tumor growth of nude mice was effectively inhibited after 6h treatment, and 6h did not cause detectable pathological abnormality of main organs.…”
Section: Discussionmentioning
confidence: 70%
“…Common patterns of MIBC involve the proliferation, migration, and invasion of bladder cancer cells. 5 - 7 During neoplastic propagation, cancer cells tend to proliferate and metastasize via the multiple steps of biological processes, including the control of signaling pathways and cell cycle. 5 - 7 Uncontrolled tumor cell proliferation is involved in the phosphorylation of mitogen-activated protein kinases (MAPKs) and phosphoinositide 3-kinase/serine-threonine kinase (PI3K/AKT) signaling.…”
Section: Introductionmentioning
confidence: 99%
“… 5 - 7 During neoplastic propagation, cancer cells tend to proliferate and metastasize via the multiple steps of biological processes, including the control of signaling pathways and cell cycle. 5 - 7 Uncontrolled tumor cell proliferation is involved in the phosphorylation of mitogen-activated protein kinases (MAPKs) and phosphoinositide 3-kinase/serine-threonine kinase (PI3K/AKT) signaling. 6 - 9 In addition, advanced type of tumor cells are significantly associated with dysregulated cell cycle control because of the changes in cell cycle regulators, such as cyclins, cyclin-dependent kinases (CDKs), and CDK inhibitors (CKIs), during the G 1 - to S-phase transition.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations